Development and implementation of a battery and solar powered DC compressor based cold storage for off grid rural areas ensuring food security - Iqbal, Anika; Faruq, Mohi Uddin; Chowdhury, Sayem; Srijan, Mehdi Hasan (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.